School Counseling Interns’ Lived Experiences Addressing Social Determinants of Health - Alexandra C Gantt; Kaprea F. Johnson; Judith W. Preston; Brittany G. Suggs; Megan Cannedy (Teaching and Supervision in Counseling, 2021)
This phenomenological study explores school counselors in training (SCITs’) experiences addressing social determinants of health (SDOH), the leading causes of educational and wellness inequities. Interviews with eight SCITs revealed three core themes: (1) professional identity conflict between awareness, skills, and action; (2) social justice knowledge to practice gap; and (3) recommendations for knowledge to practice gap resolution. Themes explained participant preparedness for responding to disparities. Participants were aware of challenges related to SDOH, though struggled with addressing those challenges due to lack of preparation or perceived role constraints. Participants also experienced difficulty practically applying their understanding of social justice theory to SDOH-related challenges. The researchers noted various recommendations for how SDOH may be addressed in the counselor education curriculum and in practice. Keywords: school counselors in training (SCIT), social justice, social determinants of health
Keywords: school counselors in training (SCIT); social justice; social determinants of health